The usefulness of National Strategies for Artificial Intelligence (SNIA): 4 case studies for decision-making as examples in Africa - (:unkn) unknown (My University, 2023)
Recent studies have demonstrated that the use of artificial intelligence (AI) can promote 3 essential sectors : economy, science and politics; when a country grasps the contribution of big data and the computing power of computers (GPU). In 2023, organizations feel obliged, given the performance of AI, to adapt to environments that are increasingly complex and difficult to anticipate. For Africa, the challenge is huge, since the majority of countries do not have national strategies dedicated to AI. This article focuses on the need to intensify public policies for AI in the continent, through robust and visionary NSAIs, while drawing their inspiration from leading countries.For Africa as for the rest of the world, public authorities could find an interest in having the keys to understanding these technologies to meet the major challenges that are already emerging in 2023. A subject that has long remained within the clan of specialists, the digital age now poses enormous challenges for citizens, science, industry and States. The speed of development of these new technologies could constitute a solution to Africa's new problems. For African countries without an AI strategy, the question that arises is how will they confront the challenges of digital transition in the event of unpreparedness by governmental authorities ? As in France, England, the USA and even in certain African countries with AI strategies, the economic and scientific benefits are already tangible in their economy in terms of an increase in their GDP.According to the French Cour des comptes, “a National Strategy is a document which sets orientations, defines priorities for action and organization, and which, when endorsed by public authorities, contains budgetary indications valid for several years ". This definition, which has a very simple echo, has always been used for other sectors since the dawn of time, when pressing opportunities had to be methodically seized. Generally speaking,
Keywords: African Research